-33=-2(1+5m)-(5+3m)

Simple and best practice solution for -33=-2(1+5m)-(5+3m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -33=-2(1+5m)-(5+3m) equation:



-33=-2(1+5m)-(5+3m)
We move all terms to the left:
-33-(-2(1+5m)-(5+3m))=0
We add all the numbers together, and all the variables
-(-2(5m+1)-(3m+5))-33=0
We calculate terms in parentheses: -(-2(5m+1)-(3m+5)), so:
-2(5m+1)-(3m+5)
We multiply parentheses
-10m-(3m+5)-2
We get rid of parentheses
-10m-3m-5-2
We add all the numbers together, and all the variables
-13m-7
Back to the equation:
-(-13m-7)
We get rid of parentheses
13m+7-33=0
We add all the numbers together, and all the variables
13m-26=0
We move all terms containing m to the left, all other terms to the right
13m=26
m=26/13
m=2

See similar equations:

| t/18+13=18 | | |2x+3|=|4x+1| | | t18+13=18 | | 4/5-(9x-20)-3x=4/5x-6 | | 3=4a+11 | | b/2+4=112 | | (8x-7)(4x+7)=0 | | 8(v+2)=16 | | (8x-7)(4x+7)=0​ | | -399=19x | | 4-(3x+7)=-33 | | 14k=-46 | | (5x−8)^2−1=48 | | 2(b+2)-5=3(b+1) | | 5x^2+3=-2x | | 9.78=1.63m | | Y=40x-600 | | 23-11=2x+2x | | 0.75x+12=7x+6 | | 3x-18=6x-18 | | 3^x=9^2x+1 | | 15-2x=-7-5x | | 1/5d-5=-2/5d+1 | | X(x-8)+11=2x-11 | | 7x-40-2x=-10 | | 76+6x=52 | | 4+k/2=7 | | (7x)+(54-x)=90 | | v−7=2 | | Y=20x-400 | | 6n+8=4n–9 | | 8/16y+48=0 |

Equations solver categories